New PP/PLA/cellulose composites: effect of cellulose functionalization on accelerated weathering behavior (accelerated weathering behavior of new PP/PLA/cellulose composites). (29th March 2015) - Darie, Raluca Nicoleta; Vlad, Stelian; Anghel, Narcis; Doroftei, Florica; Tamminen, Tarja; Spiridon, Iuliana
<x xml:space="preserve">Abstract</x> Polylactic acid (PLA) was used as partial replacement for conventional thermoplastic matrix, new composites comprising cellulose, polypropylene (PP), and PLA being realized. In order to obtain a compatible interface between cellulosic pulp and polymeric matrix, two chemical modifications of cellulose with stearoyl chloride and toluene di‐isocyanate (TDI) were performed, structural changes being evidenced by X‐ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. The composite materials were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, dynamic scanning calorimetry, impact, tensile and melt rheological tests, surface tension, and dynamic vapor sorption. Because promising results for impact strength and Young modulus were recorded when replacing 15% of PP with PLA in blends of PP with the same cellulosic pulp load, the aim of our study was to assess the behavior to accelerate weathering of composites comprising PP, cellulosic pulp, and PLA. Although the slight decrease in the mechanical properties was recorded after accelerated weathering, the use of functionalized cellulose successfully prevented the deterioration of surface materials, especially for composite comprising stearoyl chloride treated cellulose pulp. Copyright © 2015 John Wiley & Sons, Ltd.